GRAMMATICAL CHALLENGES IN LITERARY TRANSLATION (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, we analyze some grammatical issues observed in the translation of Jack London’s Martin Eden into Uzbek, undertaken by Qodir Muhammadov. This novel presents number of challenges in translation due to the structural and grammatical differences between English and Uzbek languages, which belong to different language families.